The age of hybrid events: amplifying the power of culture through digital experiences (Music Festivals feat. Technology) - Silva, Mariana Pereira da (2022)
Music festivals represent a significant part of culture as identity shapers and experience providers. With the growing use of technology in all structures of society, music festivals are not aside and have been embracing technologies as a way of creating a value offer and differentiation factor. Livestreams, cashless systems, digital events along with the use of virtual reality and social media have been ways to create a meaningful and immersive experience to the attendees and promote engagement and commitment with the music festival as a brand. This study demonstrates exactly how the implementation of technology in music festivals, thus making them hybrid, affects the overall experience of the attendee. It shows the advantages, challenges and in what specific ways it can affect the event for the promoters and the attendees, along with what aspects organizers need to acknowledge when considering embracing hybrid experiences in their festivals. It creates awareness and raises debate about this increasingly reality, providing the organization trustworthy insights about the topic of digital and/or virtual experiences.